1987
DOI: 10.1111/j.1476-5381.1987.tb11210.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular electrophysiological effects of d‐and dl‐sotalol in guinea‐pig sinoatrial node, atrium and ventricle and human atrium: differential tissue sensitivity

Abstract: 1 The effects of racemic DL-sotalol and D-sotalol on guinea-pig sino-atrial node, atrium and ventricle and on human atrium were studied using standard microelectrode techniques. Both compounds increased spontaneous sinus node cycle length largely by prolonging the repolarization phase of the action potentials. This effect was attributed to blockade of outward potassium current. 2 Ventricular action potential duration was similarly prolonged by DL-sotalol at concentrations of 5 -50 JLM.3 DL-Sotalol 1-5011M had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 17 publications
2
12
1
Order By: Relevance
“…A negative chronotropic effect of 798 has also been observed in vivo (Gwilt et al, 1989b;Yang et al, 1990). Similar negative chronotropic effects have been described for D-and L-sotalol on guinea-pig (Campbell, 1987) and rabbit (Kato et al, 1986) sinoatrial node action potentials and attributed almost entirely to prolongation of repolarization. D-Sotalol also decreased heart rate in anaesthetized dogs pretreated with propranolol in correlation with the effect on the QT-time (Mortensen et al, 1990).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A negative chronotropic effect of 798 has also been observed in vivo (Gwilt et al, 1989b;Yang et al, 1990). Similar negative chronotropic effects have been described for D-and L-sotalol on guinea-pig (Campbell, 1987) and rabbit (Kato et al, 1986) sinoatrial node action potentials and attributed almost entirely to prolongation of repolarization. D-Sotalol also decreased heart rate in anaesthetized dogs pretreated with propranolol in correlation with the effect on the QT-time (Mortensen et al, 1990).…”
Section: Discussionsupporting
confidence: 55%
“…Other drugs with class III antiarrhythmic action like amiodarone (Kadoya et al, 1985) and sotalol (Campbell, 1987) also inhibit sinus node function which may give bradycardia. It has been debated whether the negative chronotropic effect of amiodarone and sotalol could be due to their effect on repolarization alone, i.e.…”
Section: N-[4-(2-{2-[4-(methanesulphonamide)phen-mentioning
confidence: 99%
“…With respect to the effect on APD, d-sotalol exhibits greater potency on guinea pig ventricular fibers than on atrial fibers. Similar difference in tissue sensitivity was noted in an early study reported by Campbell (1987). Because I K is largely responsible for repolarization in sinus node fibers (Schram et al, 2002), it is reasonable to speculate that both HA-7-and d-sotalol-induced bradycardiac effects are due to inhibition of I K in the sinus node and that inhibition of I Ca by HA-7 may also play a part.…”
supporting
confidence: 47%
“…Campbell, 1987), has been demonstrated, by use of conventional voltage-clamp recordings, to cause dose-dependent, reversible inhibitions of guinea-pig cardiac IKv which were half-maximal at a concentration of 10pM (Carmeliet, 1985). In contrast to these observations, we found no effect of sotalol at concentrations up to 300pM on neuronal IKV in NG 108-15 cells, a finding which is consistent with the idea that sotalol exhibits tissue selectivity in its actions on I KV.…”
Section: Resultsmentioning
confidence: 99%